Towards understanding the influence of rurality on students’ access to and participation in higher education - Agumba, Hellen; Simpson, Zach; Ndofirep, Amasa (Critical Studies in Teaching and Learning, 2023)
This study examines the experiences of students from rural backgrounds in higher education in South Africa in order to foster more equitable access and participation. Edward Soja’s notion of spatial justice provides a platform for thinking about rurality and its impact on access and success in HE. Soja’s trialectical account means understanding rurality historically, spatially, and socially, and enables exploration of spatial inequalities based on the interplay between rurality and HE. Data was collected within an interpretive, qualitative, case study design through document analysis, interviews, and focus groups. The findings reveal the inequalities that students experience in HE due to their rural backgrounds and the fact that their experiences, abilities, and knowledges are neither acknowledged nor valued in the university, often by the students themselves. This study contributes to understandings of the historical, social, and spatial foundations of inequality in HE and charts future directions for policy and practice.